Isolation and Identification of Bacteria from Dumai Marine Waters that Have Potencial as Lead Bioremediation Agents - Yanti, Della Hijri; Nursyirwani, Nursyirwani; Yoswaty, Dessy (Department of Marine Science, Faculty of Fisheries and Marine Universitas Riau, 2021)
One of the harmful pollutants to human health is the heavy metal Lead (Pb). A high concentration of lead that has can accumulate in the body of living things if in a long period of time. Lead concentrations that exceed the threshold in an environment can cause damage that affects aquatic biota and other living things. This research was carried out in February-April 2021. The purpose of this study was to isolate and identify bacteria that have the potential as lead bioremediation agents from Dumai marine waters. Isolation and identification of bacteria were carried out at the Laboratory of Marine Microbiology, Department of Marine Science, Faculty of Fisheries and Marine Sciences, and the lead concentration test at the Laboratory of Chemical Testing and Analysis, Department of Chemical Engineering, Faculty of Engineering. The results of the isolation on Marine Agar media which was added with Pb acetate (Pb(CH3COO2)) obtained three bacterial isolates from Dumai sea waters, namely D1, D2, and D3. The isolate that had the best growth was isolated D1. The isolate D1 was able to reduce the highest Pb concentration from 10 ppm by 80.53%, at a concentration of 20 ppm Pb, the isolate D1 was able to reduce Pb concentration by 78.8% and at a concentration of Pb 30 ppm, isolate D1 was able to reduce Pb concentration by 77.21%.